2009
DOI: 10.3233/jcm-2009-0231
|View full text |Cite
|
Sign up to set email alerts
|

Features extraction for speech emotion

Abstract: In this paper the speech emotion verification using two most popular methods in speech processing and analysis based on the Mel-Frequency Cepstral Coefficient (MFCC) and the Gaussian Mixture Model (GMM) were proposed and analyzed. In both cases, features for the speech emotion were extracted using the Short Time Fourier Transform (STFT) and Short Time Histogram (STH) for MFCC and GMM respectively. The performance of the speech emotion verification is measured based on three neural network (NN) and fuzzy neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…A four stage ergodic hidden Markov model (HMM) is used as a classifier to accomplish this task. Performance of LFPC parameters is compared with conventional LPCC and MFCC features, and observed that LFPCs perform slightly better (Williams and Stevens 1981;Kamaruddin and Wahab 2009). The MFCC features extracted from lower frequency components (20 Hz to 300 Hz) of speech signal are proposed to model pitch variation.…”
Section: Vocal Tract Features: a Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…A four stage ergodic hidden Markov model (HMM) is used as a classifier to accomplish this task. Performance of LFPC parameters is compared with conventional LPCC and MFCC features, and observed that LFPCs perform slightly better (Williams and Stevens 1981;Kamaruddin and Wahab 2009). The MFCC features extracted from lower frequency components (20 Hz to 300 Hz) of speech signal are proposed to model pitch variation.…”
Section: Vocal Tract Features: a Reviewmentioning
confidence: 97%
“…Prosodic Yildirim et al (2004), Ververidis et al (2004), and McGilloway et al (2000) Spectral Lee et al (2001), Yildirim et al (2004), Ververidis et al (2004), and Lee and Narayanan (2005) 07 Hidden Markov models (HMM) Prosodic Fernandez and Picard (2003), Zhou et al (2001), Nwe et al (2003), and Bitouk et al (2010)SpectralWilliams and Stevens (1981),Zhou et al (2001),Nwe et al (2003), andKamaruddin and Wahab (2009) …”
mentioning
confidence: 96%
“…Further explanations of the datasets are reported in [9,10]. In this paper, only two emotion of happiness and sadness will be used to discriminate respondent excitation level.…”
Section: Data Corpusmentioning
confidence: 99%
“…The NTU-American [9,10] and The Berlin Emo-db [11] datasets representing American and European cultural influence respectively. Further explanations of the datasets are reported in [9,10].…”
Section: Data Corpusmentioning
confidence: 99%
See 1 more Smart Citation